The PAQosome, an R2TP-Based Chaperone for Quaternary Structure Formation. Issue 1 (January 2018) - Houry, Walid A.; Bertrand, Edouard; Coulombe, Benoit
Abstract : The Rvb1–Rvb2–Tah1–Pih1/prefoldin-like (R2TP/PFDL) complex is a unique chaperone that provides a platform for the assembly and maturation of many key multiprotein complexes in mammalian cells. Here, we propose to rename R2TP/PFDL as PAQosome (p article fora rrangement ofq uaternary structure) to more accurately represent its unique function.